2012
DOI: 10.1002/pmic.201200027
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of proteolytically modified proteins in human metastatic hepatocellular carcinoma cell lines reveals CAPN2 centered network

Abstract: Proteolysis affects every protein at some point in its life cycle. Many biomarkers of disease or cancer are stable proteolytic fragments in biological fluids. There is great interest and a challenge in proteolytically modified protein study to identify physiologic protease-substrate relationships and find potential biomarkers. In this study, two human hepatocellular carcinoma (HCC) cell lines with different metastasis potential, MHCC97L, and HCCLM6, were researched with a high-throughput and sensitive PROTOMAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 37 publications
(41 reference statements)
0
22
0
Order By: Relevance
“…This approach has been recently applied to analyze several proteolytic networks in humans (Niessen et al, 2011;Dix et al, 2012;Shen et al, 2012). Among others, PROTOMAP has also been used to study KLK4 substrates in a prostate cancer cell model, which identified KLK4 as a major regulator of several of TGFβ1-related proteins (Clements, 2013).…”
Section: Protein Topography and Migration Analysis Platformmentioning
confidence: 98%
“…This approach has been recently applied to analyze several proteolytic networks in humans (Niessen et al, 2011;Dix et al, 2012;Shen et al, 2012). Among others, PROTOMAP has also been used to study KLK4 substrates in a prostate cancer cell model, which identified KLK4 as a major regulator of several of TGFβ1-related proteins (Clements, 2013).…”
Section: Protein Topography and Migration Analysis Platformmentioning
confidence: 98%
“…Three stepwise human metastatic HCC cell lines with a similar genetic backgrounds, including two subclones with high (MHCC97H) and low (MHCC97L) metastatic potential from MHCC97 [23, 24] and one even higher metastatic potential cell line (HCCLM3) from MHCC97H, were established using an in vivo clonal selection procedure [25]. The pulmonary metastatic rate was 100% in MHCC97H and HCCLM3 vs. 40% in MHCC97L [26].…”
Section: Resultsmentioning
confidence: 99%
“…An initial experiment revealed that none of the metastatic cell lines suffered from significantly reduced viability after 24 h of culturing in the serum-free medium [31]. Thus, the culture time of 24 h in DMEM CM without serum was identified as the essential conditions for culturing the cells [23]. The CM was centrifuged and precipitated with TCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, calpainmediated cleavage of FAK enhances cell adhesion and cell motility (30). A recent study identified enhanced proteolysis of ezrin, vimentin, and fibronectin in a highly metastatic cell line compared to that in a nonmetastatic counterpart (37). Some of these proteins can be specifically cleaved by calpain, including ezrin (38) and vimentin (39).…”
Section: Discussionmentioning
confidence: 99%